Integration of Inclusivity Values with Entrepreneurship Education at SD Tumbuh 1 Yogyakarta - Roma Wijaya (Proceeding International Conference on Religion, Science and Education, 2023)
This research will elaborate on the integration of inclusivity values combined with entrepreneurship education at Sekolah Dasar Tumbuh 1 Yogyakarta. A glimpse of inclusive values identified as open, tolerant, and accepting behavior of others. Meanwhile, entrepreneurship has the meaning of a person's spirit, attitude, behavior, and ability to run a business or activity, increase efficiency, provide better services or generate higher profits. Therefore, the researcher will put forward the formulation of the problem, namely; how is the concept of inclusive value and entrepreneurship education, how is the implementation of the integration of inclusive values and entrepreneurship education in SD Tumbuh 1 Yogyakarta. This type of research is qualitative, then using data collection methods with interviews, documentation, and observation. The data analysis in this study used a descriptive-analytical method. With this research, it is hoped that it will become knowledgeable about the interesting collaboration between inclusive values and entrepreneurship education which are the core values of Sekolah Dasar Tumbuh 1 Yogyakarta.